First report of Olepa koslandana Orhant, 1986 (Lepidoptera: Erebidae) feeding on economically important oilseed plant castor (Ricinus communis Linnaeus) from India. (3rd April 2022) - Farooqui, Shahabab Ahmad; Siddiqua, Kazi Sabnam; Sankararaman, Hariharakrishnan; Parwez, Hina; Joshi, Rahul
ABSTRACT: In the present paper, Olepa koslandana Orhant, 1986, an Arctiid moth, is reported as a new pest feeding on flowering oilseed plant castor ( Ricinus communis L.) from the Indian region, which also reports the first association of this insect with any plant species. In addition, a list of pest species of moths that feeds on castor in India are also provided.